MATERIALS FOR A REVISION OF LAURACEAE I - A. J. G. H. KOSTERMANS (Research Center for Biology, 1968)
New species are described in Beilschmiedia (4), Cinnamomum (2),Cryptocarya (44 + one new variety), Endiandra (2), Lindera (2) and Litsea (11).New combinations are proposed in Alseodaphne (2), Cryptocarya (3),Litsea (6), Nothaphoebe (6) and Persea (2).Reductions: Cryptocarya (37), Litsea (1) and Phoebe (5).Additional material to the species is enumerated.